The impact of peer mentoring on leadership and self-efficacy in higher music education: a mixed-methods study - Wu, Zaihao; Yao, Cheng; Yang, Na (Frontiers in Psychology, 2026)
IntroductionPeer mentoring programs (PMPs) are increasingly used in higher education, yet evidence of their dual effects on mentors’ leadership and trainees’ musical self-efficacy remains limited in higher music education, particularly in non-Western conservatoire contexts.MethodsAn explanatory sequential mixed-methods design was employed. Quantitative data were collected from 32 peer mentor–peer trainee pairs (N = 64) participating in a two-month mentoring program, with leadership and musical self-efficacy measured at pretest, posttest, and one-month follow-up. Within-group changes were analyzed using repeated-measures ANOVA. Semi-structured interviews with 20 participants were conducted to further explore mentoring experiences and underlying mechanisms.ResultsPeer mentors demonstrated significant and sustained improvements in leadership behaviors, whereas leadership change among trainees was limited. In contrast, peer trainees showed substantial and sustained gains in musical self-efficacy, while mentors’ self-efficacy exhibited only modest change. Qualitative findings indicated that mentors developed greater organizational awareness and role responsibility, while trainees benefited from emotional support, targeted feedback, and vicarious learning.ConclusionThis study demonstrates that peer mentoring programs can be effectively integrated into higher music education. Participation in structured peer mentoring was associated with leadership development among mentors and improved musical self-efficacy among trainees, highlighting the value of role-based peer interaction as a complementary approach to traditional conservatoire pedagogy.